Photocleavable core cross-linked polymeric micelles of polypept(o)ides and ruthenium(ii) complexes. Issue 39 (10th August 2021) - Bauer, Tobias Alexander; Eckrich, Jonas; Wiesmann, Nadine; Kuczelinis, Felix; Sun, Wen; Zeng, Xiaolong; Weber, Benjamin; Wu, Si; Bings, Nicolas Hubert; Strieth, Sebastian; Barz, Matthias
Abstract : Functional polypept(o)ides and ruthenium(ii ) complexes are combined in photocleavable core cross-linked micelles for colloidal stability. Irradiation-induced cleavage releases the ruthenium pro-drugs and provides spatial resolution to drug delivery. Abstract : Core cross-linking of polymeric micelles has been demonstrated to contribute to enhanced stability that can improve the therapeutic efficacy. Photochemistry has the potential to provide spatial resolution and on-demand drug release. In this study, light-sensitive polypyridyl-ruthenium(ii ) complexes were combined with polypept(o)ides for photocleavable core cross-linked polymeric micelles. Block copolymers of polysarcosine- block -poly(glutamic acid) were synthesized by ring-opening N -carboxyanhydride polymerization and modified with aromatic nitrile-groups on the glutamic acid side chain. The modified copolymers self-assembled into micelles and were cross-linked by cis -diaquabis(2, 2′-bipyridine)-ruthenium(ii ) ([Ru(bpy)2 (H2 O)2 ] 2+ ) or cis -diaquabis(2, 2′-biquinoline)-ruthenium(ii ) ([Ru(biq)2 (H2 O)2 ] 2+ ). Depending on the flexibility and hydrophobicity of the nitrile linker, either small spherical structures ( D h 45 nm, PDI 0.11) or worm-like micelles were obtained. The cross-linking reaction did not affect the overall size distribution but induced a change in the metal-to-ligand charge transfer peak from 482 to 420 nm and 592 to 548 nm. The cross-linked micelles displayed colloidal stability after incubation with human blood plasma and during gel permeation chromatography in hexafluoroisopropanol. Light-induced cleavage of [Ru(bpy)2 (H2 O)2 ] 2+ was accomplished within 300 s, while [Ru(biq)2 (H2 O)2 ] 2+ could not be completely released. Analysis in HuH-7 cells revealed increased cytotoxicity via micellar delivery of [Ru(bpy)2 (H2 O)2 ] 2+ but mostly irradiation damage for [Ru(biq)2 (H2 O)2 ] 2+ . Further evaluation in ovo confirmed stable circulation pointing towards the future development of quick-release complexes.